2019
DOI: 10.12998/wjcc.v7.i16.2269
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance and diagnosis of hepatocellular carcinoma: A systematic review

Abstract: BACKGROUND Hepatocellular carcinoma (HCC) appears in most of cases in patients with advanced liver disease and is currently the primary cause of death in this population. Surveillance of HCC has been proposed and recommended in clinical guidelines to obtain earlier diagnosis, but it is still controversial and is not accepted worldwide. AIM To review the actual evidence to support the surveillance programs in patients with cirrhosis as well as the diagnosis procedure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 89 publications
0
13
0
Order By: Relevance
“…Serum AFP is the traditional tumor marker used for HCC diagnosis [5,17]. However, serum AFP levels are normal in up to 30% of HCC patients, particularly in the early stage of the disease [18].…”
Section: Discussionmentioning
confidence: 99%
“…Serum AFP is the traditional tumor marker used for HCC diagnosis [5,17]. However, serum AFP levels are normal in up to 30% of HCC patients, particularly in the early stage of the disease [18].…”
Section: Discussionmentioning
confidence: 99%
“…In the past few decades, HCC has become the fifth most common cancer with a second highest mortality rate and a poor survival outcome worldwide [ 1 ]. Several risk factors have been linked to HCC [ 2 ]; however, its prognostic predictions are yet to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…HCC is the sixth most commonly diagnosed and the fourth leading cause of cancer-related death in the world, being one of the major health challenges in liver clinic[ 65 , 66 ]. There is scarce information on the impact of COVID-19 in patients with HCC - in a small study, Zhang et al [ 67 ] reported poorer outcomes in patients with HCC but also with other malignancies when compared to the general population.…”
Section: Covid-19 and Liver Diseasesmentioning
confidence: 99%